Public Attitudes Toward Cadaveric Organ Donation: a Survey in Ahwaz - Shahbazian, Heshmatollah; Dibaei, Amir; Barfi, Maryam (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate the attitudes of the residents of Ahwaz toward organ donation after brain death. Materials and Methods: A total of 1000 people between 15 and 70 years of age were selected by cluster sampling in Ahwaz, south-west of Iran. A questionnaire was designed about the attitudes of the interviewees toward organ donation after brain death by themselves and by their family members, demanding compensation for organ donation, and the need for consent or testimony. Results: Of the participants, 75% were pro organ donation, while 22% were against it and the remaining 3% had no specific idea. Age, sex, and occupation did not influence the attitudes; however, the ethnicity, educational level, economic status, and having a loved one in need of organ transplantation significantly increased the willingness of these people for organ donation (P < .05). Regarding the issue of demanding compensation for organ donation, 27% of the participants were in favor of the idea and 73% disagreed. A higher proportion of the participants with higher educational levels believed in organ donation without any consent or testimony (P = .02). Conclusion: According to our study, many people are pro organ donation after death. It is necessary to have a regular program for these people to give them the opportunity to register and receive a donation card. For the people who do not have the tendency for the matter, we had better try to increase their knowledge by educational programs and provide sufficient information.